Structuring oil to substitute palm fat in dry-fermented poultry sausages. (July 2022) - Dreher, Johannes; Knorz, Marius; Herrmann, Kurt; Terjung, Nino; Gibis, Monika; Weiss, Jochen
Abstract: Canola oil was structured by incorporation into a transglutaminase-induced covalently crosslinked network of soy proteins in order to mimic characteristics of animal fat tissue. Wheat fibers (3% and 6%) with fiber lengths of 30, 150, and 400 µm were added, which increased hardness, but did not notably affect the desired elastic properties. The animal fat mimetics containing wheat fibers showed a decreased tendency to fracture into small pieces under strong deformation. Some of the animal fat mimetics were then taken to replace palm fat from the formulation of dry-fermented poultry sausages. No differences in pH decrease by fermentation were observed, regardless of the type of fat system used. Fat particles within the sausages' meat matrix were clearly and distinctly visible when wheat fibers were added to strengthen their structure, visibly resembling an authentic fat marbling for salami-type sausages. As the weight loss of the sausages progressed, reduction of water from these fat particles led to a slight decrease in the whitish appearance, indicating that improved stabilization might be necessary for sliced products. As palm fat has a higher hardness and less elastic properties, compared to animal fat mimetics, this was reflected in the sausages' texture as well. Highlights: Canola oil was structured to mimic animal fat tissue. Addition of wheat fibers increased firmness and reduced fracturability. Animal fat mimetics were used to replace palm fat in dry-fermented poultry sausages. Fat particle distribution was improved when wheat fibers were added to fat mimetics.